(untitled) (Praxis Educativa, 2022)
We present a first systematization of an in-service teacher training process, arising from the articulation between a socio-territorial organization and a school in the Paraná Delta. This territory of extensive wetlands is crisscrossed by disputes between on one side rural living spaces and islander ways of life and on the other side privatization and transformation into luxury gated communities with serious socio-environmental consequences. We intend to contribute to the understanding of some ways in which these socio-territorial movements can contribute to the pedagogical-didactic frameworks that sustain dialogues between school and communities. In particular, we analyze the contributions to the pedagogization of environmental conflicts